INVESTIGATION THE KINEMATICS OF MOUNTAIN BUILDING IN TAIWAN FROM THE SPATIOTEMPORAL EVOLUTION OF THE FORELAND BASIN AND WESTERN FOOTHILLS - Simoes M.; Avouac J.P. (My University, 2006)
The Taiwanese range has resulted from the collision between the Luzon volcanic arc and the Chinese continental margin, which started about 6.5 Myr ago in the north, and has since propagated southward. The building of the range has been recorded in the spatiotemporal evolution of the foreland basin. We analyze this sedimentary record to place some constraints on the kinematics of crustal deformation. The flexure of the foreland under the load of the growing wedge started with a 1.5 Myr long phase of rapid subsidence and sedimentation, which has migrated southward over the last 3.5 Myr at a rate of 31 +101-5 mm/yr, reflecting the structural evolution of the range and the growth of the topography during the oblique collision. Isopachs from the Toukoshan (~0 to 1.1 Ma) and Cholan (~1.1 to 3.3 Ma) formations, as well as the sedimentation rates retrieved from a well on the Pakuashan anticline, indicate that the foreland basement has been moving toward the center of mass of the orogen by ~45-50 mm/yr during the development of the basin. From there, we estimate the long-term shortening rate across the range to 39.5-44.5 mm/yr. By considering available data on the thrust faults of the foothills of central Taiwan, we show that most (if not all) the shortening across the range is accommodated by the most frontal structures, with little if any internal shortening within the wedge. The range growth appears therefore to have been essentially sustained by underplating rather than by frontal accretion. In addition, only the upper ~7 to 9 km of the underthursted crust participates to the growth of the orogen., This requires that a significant amount of the Chinese passive margin crust is subducted beneath the Philippine Sea plate. Copyright 2006 by the American Geophysical Union.